2016
DOI: 10.2147/ppa.s110903
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in patients with type 2 diabetes mellitus: the role of anxiety, depression, and glycemic control

Abstract: ObjectiveThis study was aimed at determining the prevalence of alexithymia in patients with type 2 DM and the factors affecting it.MethodsThis cross-sectional study was conducted with 326 patients with type 2 DM. Study data were collected with the Personal Information Form, Toronto Alexithymia Scale, and Hospital Anxiety and Depression Scale. Glycemic control was assessed by glycated haemoglobin (HbA1c) results. The analysis was performed using descriptive statistics, chi-square test, Pear-son’s correlation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…A number of investigative groups have reported epigenetic biomarkers (DNA methylation, microRNAs [miRNAs], and long noncoding RNAs [lncRNAs]) associated with the occurrence of depression; for example, some specific lncRNAs may have the ability to regulate major depression 1 . Many studies have shown that type 2 diabetes mellitus (T2DM) is closely related to the onset and progression of depression 2 4 , and several other reports have described the relationships between depression and T2DM 5 7 . However, the molecular pathophysiology, particularly the epigenetic regulation, of this association is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigative groups have reported epigenetic biomarkers (DNA methylation, microRNAs [miRNAs], and long noncoding RNAs [lncRNAs]) associated with the occurrence of depression; for example, some specific lncRNAs may have the ability to regulate major depression 1 . Many studies have shown that type 2 diabetes mellitus (T2DM) is closely related to the onset and progression of depression 2 4 , and several other reports have described the relationships between depression and T2DM 5 7 . However, the molecular pathophysiology, particularly the epigenetic regulation, of this association is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We found that most included studies were conducted in Italy (three out of seven), and pertained to cross-sectional research studies. Specifically, four studies adopted a one-sample research design (Luca et al, 2015 ; Avci and Kelleci, 2016 ; Lai et al, 2019 ; Martino et al, 2019a ), whereas three studies also included comparison groups referring to healthy controls (Shahi and Mohammadyfar, 2017 ; Fares et al, 2019 ) or patients with T1DM (Melin et al, 2017 ). Five studies reported specific inclusion/exclusion criteria for patient selection (Avci and Kelleci, 2016 ; Melin et al, 2017 ; Fares et al, 2019 ; Lai et al, 2019 ; Martino et al, 2019a ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, four studies adopted a one-sample research design (Luca et al, 2015 ; Avci and Kelleci, 2016 ; Lai et al, 2019 ; Martino et al, 2019a ), whereas three studies also included comparison groups referring to healthy controls (Shahi and Mohammadyfar, 2017 ; Fares et al, 2019 ) or patients with T1DM (Melin et al, 2017 ). Five studies reported specific inclusion/exclusion criteria for patient selection (Avci and Kelleci, 2016 ; Melin et al, 2017 ; Fares et al, 2019 ; Lai et al, 2019 ; Martino et al, 2019a ). The most reported inclusion criterion was having good language proficiency to fully comprehend or perform the psychological administration (Melin et al, 2017 ; Fares et al, 2019 ; Lai et al, 2019 ; Martino et al, 2019a ).…”
Section: Resultsmentioning
confidence: 99%
“…Depression is highly prevalent among patients with DM, and several studies have shown that DM is associated with depressive symptoms . In addition, depression is related to current age, duration of DM, age at diagnosis of DM, secondary education, poor DM control, high BMI score, being single, high HbA1c level, and the course of disease . In addition, some recent studies showed that preDM was associated with depression symptoms .…”
Section: Discussionmentioning
confidence: 99%